Theory and practice of counseling and psychotherapy - Corey, Gerald. 4 0 16; 5 (Australia : Brooks/Cole/Cengage Learning, 2009)
Explains various theories used in counseling, offers a case study that runs throughout the text to describe how they are applied, and includes recommended supplementary readings.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Counseling.;Psychotherapy. -- 20; 20; 2